Recombinant feline interferon omega therapy in cats naturally infected with Feline Immunodeficiency Virus : clinical, viral and immunological relevance - Leal, Rodolfo Assis Oliveira (2014)
Tese de Doutoramento em Ciências Veterinárias Especialidade de Clínica